2013
DOI: 10.1007/s11467-013-0321-0
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Bose-Einstein condensates in a one-dimensional optical lattice with double-well potential

Abstract: We study dynamical behaviors of the weakly interacting Bose-Einstein condensate in the onedimensional optical lattice with an overall double-well potential by solving the time-dependent Gross-Pitaevskii equation. It is observed that the double-well potential dominates the dynamics of such a system even if the lattice depth is several times larger than the height of the double-well potential. This result suggests that the condensate flows without resistance in the periodic lattice just like the case of a single… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Instead, some studies have developed novel analytic methods [34][35][36][37]. On the other hand, for BECs in shallow optical lattices, theoretical analysis of phase decoherence in 1D has been extensively performed via an extended Gross-Pitaevskii equation (GPE) approach [38], or via the Truncated Wigner Approximation (TWA) approach [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, some studies have developed novel analytic methods [34][35][36][37]. On the other hand, for BECs in shallow optical lattices, theoretical analysis of phase decoherence in 1D has been extensively performed via an extended Gross-Pitaevskii equation (GPE) approach [38], or via the Truncated Wigner Approximation (TWA) approach [31].…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, theoretical studies in deep lattices have used the Bose-Hubbard model (BHM) [18-20, 23, 24, 32] or Time-Evolving Bloch Decimation (TEBD) approach [33], both of which become problematic when there are many atoms per well, as in the one-component experiments of [7]. Instead, some studies have developed novel analytic methods [34][35][36][37]. On the other hand, for BECs in shallow optical lattices, theoretical analysis of phase decoherence in 1D has been extensively performed via an extended Gross-Pitaevskii equation (GPE) approach [38], or via the Truncated Wigner Approximation (TWA) approach [31].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, scientists have performed much theoretical and experimental research in the field of BECs after a BEC was first observed in dilute alkali gases. Rich phenomena have been revealed in the studies of BEC, such as solitons [2,3], vortex formation [4,5], Josephson oscillation [6,7], chaos [8], and symmetry breaking [9][10][11][12]. The matter-wave soliton was also experimentally observed in ultra-cold atom gases [13,14], and with the development of Feshbach resonance [15][16][17], it plays a crucial role in the research on solitons [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%